2018
DOI: 10.1111/ijpp.12490
|View full text |Cite
|
Sign up to set email alerts
|

Moral dilemmas reflect professional core values of pharmacists in community pharmacy

Abstract: Objectives The aim was to recognise the professional core values in the moral dilemmas of pharmacists in community pharmacy and to customise the descriptions of these values for community pharmacy practice. Methods The narratives of 128 moral dilemmas, collected from Dutch PharmD students and early career pharmacists who experienced these dilemmas in practice, were qualitatively analysed. An expert panel deductively coded relevant portions of these narratives with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The charter states the profession's core values, which guide pharmacists working in all sectors in the Netherlands. Commitment to the patient's well-being, which includes protecting the patient's rights, is an important value, but so are societal responsibility, being reliable and caring, pharmaceutical expertise and professional autonomy [40]. One core value is not more important than another.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The charter states the profession's core values, which guide pharmacists working in all sectors in the Netherlands. Commitment to the patient's well-being, which includes protecting the patient's rights, is an important value, but so are societal responsibility, being reliable and caring, pharmaceutical expertise and professional autonomy [40]. One core value is not more important than another.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, different statements representing the post-conventional moral reasoning schema triggered the pharmacists in both countries, suggesting variation in underlying beliefs and cognitions and pharmacy practice context. This is surprising as in both countries pharmacists have a patient-centred pharmaceutical care practice as their highest goal [40,41]. However, the variation may come from differences in professional guidance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Values encompass many other objectives already embraced by the healthcare, such as: quality, safety, focus on patients, cost containment and their integration. Kruijtbosch et al [27] suggested the following values as foundational to pharmacy practice as well as any other healthcare practice: self-determination, compassion, justice, respect for persons, commitment to integrity and ethical practice and commitment to excellence [27,33].Values could be important for the study of pharmacists' behaviour because they could help us understand attitudes, perceptions and motivations. Also, perception of ethical issues could be affected by the values of pharmacists.…”
Section: Introductionmentioning
confidence: 99%
“…6,[14][15][16][17] An "ethical dilemma" is operationalized as a "situation in which there is a choice between at least two courses of action, neither of which is morally correct". 18 Community pharmacy professionals in different countries are experiencing frequent and complex ethical dilemmas which compromise ethical pharmacy practice. 6,8,15,[19][20][21] They often run a commercial matter nearby their work sites which further augment the dilemmas.…”
Section: Introductionmentioning
confidence: 99%